2013
DOI: 10.1371/journal.pone.0064811
|View full text |Cite
|
Sign up to set email alerts
|

A Focused Ethnographic Study of Alberta Cattle Veterinarians’ Decision Making about Diagnostic Laboratory Submissions and Perceptions of Surveillance Programs

Abstract: The animal and public health communities need to address the challenge posed by zoonotic emerging infectious diseases. To minimize the impacts of future events, animal disease surveillance will need to enable prompt event detection and response. Diagnostic laboratory-based surveillance systems targeting domestic animals depend in large part on private veterinarians to submit samples from cases to a laboratory. In contexts where pre-diagnostic laboratory surveillance systems have been implemented, this group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…Based on discussion from a focus group of practicing veterinarians, Robinson et al ( 53 ) found that the high costs associated with performing diagnostic tests deterred sample submission, although producers were more willing to submit samples if the veterinarian was unsure of the diagnosis, if the disease was having a significant economic impact, or if the problem was not resolving with empirical treatment. Similar findings have been reported elsewhere ( 51 , 54 ).…”
Section: Data Streamssupporting
confidence: 93%
See 3 more Smart Citations
“…Based on discussion from a focus group of practicing veterinarians, Robinson et al ( 53 ) found that the high costs associated with performing diagnostic tests deterred sample submission, although producers were more willing to submit samples if the veterinarian was unsure of the diagnosis, if the disease was having a significant economic impact, or if the problem was not resolving with empirical treatment. Similar findings have been reported elsewhere ( 51 , 54 ).…”
Section: Data Streamssupporting
confidence: 93%
“…The population coverage of laboratory submission data can be influenced by practitioner perceptions and experience ( 51 ) as well as the financial and epidemiological state of the livestock industry ( 52 ). Based on discussion from a focus group of practicing veterinarians, Robinson et al ( 53 ) found that the high costs associated with performing diagnostic tests deterred sample submission, although producers were more willing to submit samples if the veterinarian was unsure of the diagnosis, if the disease was having a significant economic impact, or if the problem was not resolving with empirical treatment.…”
Section: Data Streamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insights from the analysis of surveillance reports and participant feedback highlight important considerations for transitioning the pilot program to a sustainable large-scale and multi-species surveillance system. Other veterinary practitioner-based surveillance systems have used financial incentives such as laboratory testing credits (32) and direct financial compensation (41) to encourage user participation. Although this has been highlighted as an important incentive for some veterinarians (31), it may not be sustainable depending on long-term funding availability.…”
Section: Discussionmentioning
confidence: 99%